2008
DOI: 10.1021/la7033438
|View full text |Cite
|
Sign up to set email alerts
|

Functional PEG-Modified Thin Films for Biological Detection

Abstract: We report a general procedure to prepare functional organic thin films for biological assays on oxide surfaces. Silica surfaces were functionalized by self-assembly of an amine-terminated silane film using both vapor- and solution-phase deposition of 3'-aminopropylmethyldiethoxysilane (APMDES). We found that vapor-phase deposition of APMDES under reduced pressure produced the highest quality monolayer films with uniform surface coverage, as determined by atomic force microscopy (AFM), ellipsometry, and contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 49 publications
2
93
0
Order By: Relevance
“…The development of methods to tune the surface properties of two robust high bandgap materials, silicon-rich silicon nitride (SixN4, 3.5 < x < 4.5) and SiC would significantly increase the possible use of these materials. SixN 4 is widely used, for example, as waveguide material in refractometric (McDonagh et al, 2008) or fluorescence (Anderson et al, 2008) detection, and as coating material for sensors based on electrical impedance (Tlili et al, 2005) or vibrating microcantilevers (Goeders et al, 2008) SiC has a high potential for similar applications (Yakimova et al, 2007). For such sensing and biomedical applications, both materials would benefit from specific surface modification.…”
Section: Surface Functionalizationmentioning
confidence: 99%
“…The development of methods to tune the surface properties of two robust high bandgap materials, silicon-rich silicon nitride (SixN4, 3.5 < x < 4.5) and SiC would significantly increase the possible use of these materials. SixN 4 is widely used, for example, as waveguide material in refractometric (McDonagh et al, 2008) or fluorescence (Anderson et al, 2008) detection, and as coating material for sensors based on electrical impedance (Tlili et al, 2005) or vibrating microcantilevers (Goeders et al, 2008) SiC has a high potential for similar applications (Yakimova et al, 2007). For such sensing and biomedical applications, both materials would benefit from specific surface modification.…”
Section: Surface Functionalizationmentioning
confidence: 99%
“…This study also concluded that PEG-modified surfaces retain their protein and cell repulsive nature for the period of investigation, i.e., 28 days (Sharma et al, 2004). With regard to PEG stability in the air, no degradation was reported after 75 days (Anderson et al, 2008). In contrast to these macroscopic experimental studies, PEG-coated surfaces used for singlemolecule imaging imposes several challenges.…”
Section: Stability Of Peg-coated Surfacesmentioning
confidence: 74%
“…Miniaturized microfluidics sensors, for example, can use silicon oxide or silicon nitride as waveguide and immobilization platform. In particular, Si x N 4 is widely used, for example, as waveguide material in refractometric [Karymov, et al, 1995] or fluorescence [Anderson, et al, 2008] detection. Among all optical techniques, one type of surface-based detection technique, surface plasmon resonance (SPR), has had magnificent success in the last 20 years [Phillips, K.S.…”
Section: Biodetection Based On Organic Monolayers On Surfacesmentioning
confidence: 99%